2014
DOI: 10.1037/neu0000026
|View full text |Cite
|
Sign up to set email alerts
|

Preserved, deteriorated, and premorbidly impaired patterns of intellectual ability in schizophrenia.

Abstract: Objective: Although impaired general intellectual ability is a prevalent feature in schizophrenia, patterns suggesting preserved, deteriorated, and premorbidly impaired intellect have also been identified. The main purpose of this investigation was to examine the clinical, cognitive, and neuroanatomical characteristics of these intellectual subtypes, and to establish the value and validity of this approach for reducing the heterogeneity of schizophrenia. Methods: A total of 71 patients with a diagnosis of schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 171 publications
(274 reference statements)
2
18
1
2
Order By: Relevance
“…On the other hand, 30.5% of patients had an intact cognitive function. This finding is higher than previous studies that reported 19–28% of patients with psychosis found to have an intact cognitive function . This discrepancy may be due to the difference in duration of follow‐up, cognitive assessment tools, use of composite score, and level of cognitive function at baseline.…”
Section: Discussioncontrasting
confidence: 76%
“…On the other hand, 30.5% of patients had an intact cognitive function. This finding is higher than previous studies that reported 19–28% of patients with psychosis found to have an intact cognitive function . This discrepancy may be due to the difference in duration of follow‐up, cognitive assessment tools, use of composite score, and level of cognitive function at baseline.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, a premorbid–current ability discrepancy score was created by transforming the Reading standard score into a T score and subtracting the MCCB composite T score from this value. Similar discrepancy scores have been used to index premorbid–current ability differentials by Ammari et al (2014) , Badcock et al (2005) , Harvey et al (2006) and O’Connor et al (2012) . Clinical state and symptom severity were measured with the Positive and Negative Syndrome Scale (PANSS; Opler et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, an average-range IQ may not represent normal cognition if performance prior to illness onset was above average. Proxy measures of premorbid ability like reading skill reveal declines when compared with current ability in many schizophrenia patients ( Ammari et al, 2014 , Weickert et al, 2000 ). It follows that differences in estimated premorbid ability may exist between patients and controls even when there are no differences in current ability.…”
mentioning
confidence: 99%
“…The degree of intelligence decline in patients with schizophrenia is typically classified into three intellectual levels [18,23,47,69,71,72,73,74,75,76,77]:Deteriorated group: patients with a difference of 10 points or more between premorbid IQ and present IQ;Preserved group: patients with a difference of less than 10 points between premorbid IQ and present IQ (premorbid IQ above 90);Compromised group: patients with a difference of less than 10 points between premorbid IQ and present IQ (premorbid IQ below 90).…”
Section: Intelligence Decline In Schizophreniamentioning
confidence: 99%